Cyclic regulation of transcription factor C/EBP beta in human endometrium - Young Steven L; Bagchi Milan K; Yuan Lingwen; Kannan Athilakshmi; Plante Beth J (BMC, 2009)
Abstract Background The transcription factor CCAAT/enhancer-binding protein (C/EBP) beta is a critical mediator of murine endometrial function during embryo implantation. Our objective is to characterize changes in C/EBP beta mRNA abundance and protein localization over the normal human menstrual cycle. Methods Fifty normally cycling volunteers without reproductive disorders were randomized to undergo endometrial sampling on a specific cycle day, with secretory phase samples timed using urinary LH surge. Samples were assessed for relative C/EBP beta mRNA expression using quantitative real-time RT-PCR and for C/EBP beta protein localization using immunohistochemistry. The semiquantitative histologic scoring (HSCORE) system was used to compare staining intensity in each tissue compartment between each cycle phase. Results C/EBP beta mRNA expression by whole endometrium peaks in the late secretory phase and is significantly higher than that in the proliferative and mid-secretory phases. A marked increase in nuclear C/EBP beta protein immunostaining is seen in stromal cells beginning about cycle day 20, coincident with the start of endometrial receptivity. This increased staining continues for the remainder of the cycle. Conclusion In the normal human menstrual cycle, C/EBP beta mRNA and protein expression also change, with increased nuclear immunostaining in the mid-secretory phase, suggesting a possible role for C/EBP beta in human endometrial receptivity.